The Role of Religion in Shaping Medieval European Society - Rossi, Daniel (International Journal of History Research, 2024)
Purpose: The aim of the study was to analyze the role of religion in shaping medieval European society. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Religion profoundly shaped medieval European society, with Christianity, particularly Catholicism, serving as a dominant force. The Church wielded authority over governance, morality, and culture, influencing daily life and socio-political structures. Religious institutions constructed grand edifices, symbolizing devotion and societal wealth. Yet, religious fervor also fueled conflicts like the Crusades. Despite its power, challenges to religious authority, such as the Protestant Reformation, underscored ongoing tensions between spiritual doctrine and individual autonomy. Unique Contribution to Theory, Practice and Policy: Dependency Theory, Marxist Theory & Modernization Theory may be used to anchor future studies on the role of religion in shaping medieval European society. Emphasize the importance of understanding diverse religious traditions and fostering mutual respect and tolerance among different religious communities. Incorporate the study of religion into school curricula at all levels to promote religious literacy, critical thinking, and understanding of diverse cultural perspectives.